Field evaluation of bread and durum wheat varieties for Septoria Tritici Blotch resistance in Morocco - Maafa, Ilyass; Bentata, Fatiha; Labhilili, Mustapha.; Kemal, Seid Ahmed; El Aissam, Aicha (2024)
Septoria tritici blotch (STB) caused by Zymoseptoria tritici, is one of the devastating foliar diseases on bread and durum wheat production in Morocco. It causes up to 50% yield losses where susceptible wheat varieties are grown under weather conditions conducive to STB development. Farmers integrate growing moderately resistant varieties with additional sprays with fungicides. There are reports of Z. tritici isolates resistant to quinone outside inhibitor (QoIs) : a widely used group of fungicides in wheat disease management (1 & 2). The continuous virulence evolution of Z. tritici populations leads to losses of resistance in popular wheat varieties. The objective of this study was to assess if there are changes in the resistance of Moroccan wheat varieties released between 1982-2003 to the current field pathogen populations